Running Lean, 3rd Edition - Maurya, Ash (O'Reilly Media, Inc., 2022)
We're building more products today than ever before, but most of them fail--not because we can't complete what we want to build but because we waste time, money, and effort building the wrong product. What we need is a systematic process for quickly vetting product ideas and raising our odds of success. That's the promise of Running Lean. In this inspiring book, Ash Maurya takes you through an exacting strategy for achieving a product/market fit for your fledgling venture. You'll learn ideas and concepts from several innovative methodologies, including the Lean Startup, business model design, design thinking, and Jobs-to-be-Done. This new edition introduces the continuous innovation framework and follows one entrepreneur's journey to uncover, design, and build a product that matters. Know when to "pivot" by changing your plan's course Maximize your efforts for speed, learning, and focus Learn the ideal time to raise your "big round" of funding Find a problem worth solving, then define a solution Engage your customers throughout the development cycle Continually test your product with smaller, faster iterations Build a feature, measure customer response, and verify or refute the idea.